PENGARUH FAKTOR SOSIAL-EKONOMI TERHADAP STATUS KEMISKINAN RUMAH TANGGA PERTANIAN DI ACEH - Mursalina Mursalina; Melly Melly (Jurnal Agrisep, 2016)
Poverty rate in Aceh especially on agriculture household is still very high. This research aim to know the relationship and the effect of characteristics household on the agriculture household poverty status. This research uses analysis of chi-square independency test and logistic regression. The results of chi-square test showed that from 16 variables tested, one variable is sex of household head dont have relationship with poverty status. The results of logistic regression analysis showed that there were 8 variables significantly influence on poverty status agriculture household consisting of demographic characteristics, housing and assets. They are age of household head, household size, house status, house size, water drink source (well water), cooking fuel (firewood and LPG 3 kg), and motorcycle ownership. While, education characteristics and employment do not have significantly influence on poverty status. For reducing poverty especially on the agriculture household, the government should look the indicators of poverty so the poverty alleviation programme become more effective.